El eje fecundatorio norte-sur del Perú: una interpretación psicológica - León, Federico (1984)
The north-south fecundity axis consists of an ordinal relationship between a geographic dirnension (northern, central and southern planning regions of Peru) and the desire of children of Peruvian women, the desire being greater among northerners and smaller among southerners. Correlational, covariance, and regression analyses were Rerformed on the ENPA data bank (N = 6,437) in order to determine for the women with children of North, Center, and South (N= 1,765) whether the north-south fecundity axis could be accounted for by such variables as altitude/culture (coast, mountain), urbanization, education, income, work, conjugality, number of children alive, and number of children dead. The north-south fecundity axis proved to be independent of these variables,. although some interactions approached statistical sígnificance. A psychological interpretation of the findings was proposed. The northern woman would desire more children because of her greater acceptance of a dependent feminine role and a disposition to please her husband's machismo. The southern woman would desire less children because of her more autonomous outlook in family life and greater expectations of active participation in occupational roles.